Sexual Divisions of Labor in Export-Oriented Manufacturing Sectors: The Reconstruction of Gender and the Urbanization of Production in the Global South - Pepper, Analee (Consilience, 2012)
The feminization of labor in parallel with the feminization of poverty in poor countries is a controversial topic in the field of development, especially with regards to foreign-owned export-oriented manufacturing sectors (FEMS). This paper offers a critique of the dominant argument that the introduction or expansion of a poor county’s FEMS will positively affect the status of women, thereby stimulating sustainable human development. I argue that intersecting oppressions (i.e. female, poor, immigrant, rural, dark skinned) are exploited and exaggerated in order to achieve economic interests. International development groups such as the World Bank have labeled FEMS in poor countries as opportunities for women to increase their independent earning power and socioeconomic status. This is based on the logic that gender equality—a factor believed to stimulate development—is only achieved through access to the formal labor sector and independent capital earnings. However, this neglects the underlying fact that for FEMS to be economically sustainable, gender inequality, as well as global economic inequality, must remain unchanged. In addition to this critique, this paper attempts to answer the following questions: What are the different ways in which poor women in the Global South are impacted by the influx of export-oriented manufacturing industries? How is gender constructed and utilized within these industries’ managerial policies? What are the ensuing effects of this on the labor force?